If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2+3x-(5-2x)=8
We move all terms to the left:
2+3x-(5-2x)-(8)=0
We add all the numbers together, and all the variables
3x-(-2x+5)+2-8=0
We add all the numbers together, and all the variables
3x-(-2x+5)-6=0
We get rid of parentheses
3x+2x-5-6=0
We add all the numbers together, and all the variables
5x-11=0
We move all terms containing x to the left, all other terms to the right
5x=11
x=11/5
x=2+1/5
| x^2+12x=589 | | 12,6-b=-5b | | 12,6-b=5b | | 4y-13=34 | | -13=-7x+5 | | 4(3f−2)=20 | | q^-2/3=9 | | 0,5k=-81-2,5k | | 2*14-6x+1=2x-1 | | 0=4x3-40x2+96x-80 | | 124=5/6x+x | | 3x^2=11x+24 | | 51=x=180 | | -2x+2+4x=-10 | | -4x+9+7x=45 | | -2(-6+6x)=-48 | | -3(7-2x)=-33 | | 1/8(16k+8)=-5 | | 4x+8=58+3x | | 2x+5^(-x)=4 | | 7^3x=49^x-1 | | 0.5×x×x×x+3×x+8=0 | | n*8+3=26 | | 5(4x+8)-2(4-6x)=0 | | (1.2x+3.8)/4=(5.2x+1.8)/6 | | 40y-7=12y^2 | | -14=8-5x | | 5(3n-1)=55 | | 3(9+4x)=123 | | 2y-8=22-4y | | 2(7x-10)=36 | | 3x+2(x+7)=-11 |